Analisis Strategi Penerjemahan Istilah Budaya pada Buku Cerita Anak dari Platform Let’s Read Asia - Winda Rizky Fatma Sari; Misyi Gusthini (LPPM Universitas Terbuka, 2023)
Children need a book that has moral values and provides opportunities for them to explore their imagination and their childhood world. Today, there are many translated books from various backgrounds in the world. Translated children's story books must be communicative in nature so that they are easy to understand and are able to attract children's attention, as well as provide a pleasant experience while reading. However, there are often obstacles to translation, one of which is cultural translation. For this reason, it is necessary to have an appropriate strategy for translating these cultural terms, especially story books for children. This research aims to analyze the translation strategies for cultural terms found in four selected children's story books from the digital library Let's Read Asia – The Asia Foundation so that the translators can take it as things into consideration to translate similar terms. These cultural terms are classified into five categories of cultural words according to Newmark (1988), then the translation strategies are identified. The author refers to the theory of cultural translation strategies from several experts such as Newmark (1988), Baker (2011), and Hoed (2006), some of whose strategies are similar to one another.